Visutá lávka pro pěší přes řeku - Chumová, Petra (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Předmětem diplomové práce je návrh lávky pro pěší přes koryto řeky. Pro zadaný problém byly vytvořeny tři variantní studie. K podrobnému zpracování byla vybrána visutá lávka pro pěší. Hlavní náplní práce je statické řešení nosné konstrukce. Model konstrukce pro výpočet účinků vybraných zatížení včetně zahrnutí vlivu výstavby mostu, byl vytvořen ve výpočetním programu Ansys. Posouzení a dimenzování proběhlo ručním výpočtem dle zásad mezních stavů a platných norem.

The subject of the thesis is to design a suspension footbridge over a river basin. Three different studies were created for the assigned problem. The suspension footbridge was chosen for the thorough elaboration. The most important part of the thesis is the static solution of the supporting structure. The structure model for calculation of impacts of selected strains including the impact of the footbridge construction was created in computational software Ansys. Assessment and dimensioning was carried out using manual calculation according the principles of limit states and applicable standards.
Suspension footbridge across the river
Keywords: lávka pro pěší; visutá konstrukce; lano; segment; pylon; beton; předpětí; footbridge; suspension structure; cable; segment; tower; concrete; prestressing